Dinamika dan Profil Undecided Voters Menjelang Pemilu 2024 di Indonesia - Priyatno, Vincentius Gitiyarko (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
Leading up to the 2024 elections, the public is starting to show their political preferences for both presidential candidates and political parties. However, there is still a portion of the population that hasn't disclosed their choices. Unlike abstaining from voting (golput), this position is more temporary, given that there is still time to consider their options for the upcoming elections. In surveys, this position is indicated by responses such as "don't know," "no answer," or keeping their choice secret when asked about which figure or party they will vote for in the elections. The August 2023 survey by Litbang Kompas indicates that this group is still around 11.6 percent. Considering the 4 percent threshold for a political party to enter parliament, this is a significant number. Additionally, for the presidential choice, 27.9 percent of respondents are still undecided. The research methodology employed in this study is quantitative, using a survey of respondents across Indonesia (N:1364). Data analysis involves descriptive statistical analysis by compiling frequency tables with several cross-tabulations. A comparison with previous survey results is also conducted to show trends. This research also describes the profile of undecided voters in terms of gender, age, education level, and respondent's area of residence for both presidential and political party choices.Menjelang pemilu 2024, masyarakat mulai menunjukkan preferensi politik mereka terhadap pilihan presiden maupun pilihan partai politik. Namun, masih ada sebagian publik yang belum menunjukkan pilihannya. Berbeda dengan golput, posisi ini lebih temporer mengingat masih ada waktu untuk mempertimbangkan pilihan dalam pemilu nantinya. Dalam survei, posisi ini ditunjukkan dengan pilihan jawaban tidak tahu, tidak jawab, atau rahasia saat ditanya tokoh siapa maupun partai apa yang akan dipilih dalam pemilu. Survei Litbang Kompas Agustus 2023 menunjukkan kelompok ini masih sekitar 11,6 persen. Mengingat ambang batas sebuah partai politik masuk ke dalam parlemen adalah 4 persen, maka jumlah tersebut tidaklah sedikit. Ditambah lagi, untuk pilihan presiden, masih ada 27,9 persen responden yang belum menentukan pilihan. Metode penelitian yang digunakan dalam penelitian ini adalah kuantitatif dengan survei terhadap sampel responden di seluruh Indonesia (N=1364).Â  Sedangkan analisa data menggunakan analisis statistik deskriptif dengan menyusun tabel frekuensi dengan beberapa krostabulasi. Dilakukan juga pembandingan antara hasil survei sebelumnya untuk menunjukkan tren. Penelitian ini juga mendeskripsikan profil undecided voters dari sisi jenis kelamin, usia, tingkat pendidikan, serta wilayah domisili responden baik untuk pilihan presiden maupun partai politik.